1986
DOI: 10.1111/j.1365-2621.1986.tb00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Frozen storage life of the Bolivian fish, sabalo (Prochilodus platensis)

Abstract: A supply of the Bolivian fish sabalo, Prochilodw platensis, was stored at -15 " and -30 "C. Samples were taken at intervals for analysis and taste panel assessment. No significant change was observed in 20 months at either temperature in the pH or in the percentage of protein soluble in 5% sodium chloride. The fish remained acceptable to the taste panel throughout. Thus the storage life of the species is shown to be in excess of 20 months at both -15 " and -30 "C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…There was a little difference in the proximate composition of red mullet (79.06% moisture, 19.63% protein, 1.01% fat and 0.98% ash) compared with the findings by Curran et al (1986). Aubourg (2004a, b) reported that the chemical composition of horse mackerel was 74-76.80% moisture, and 2.2-0.70% total fat.…”
Section: Proximate Compositionmentioning
confidence: 70%
“…There was a little difference in the proximate composition of red mullet (79.06% moisture, 19.63% protein, 1.01% fat and 0.98% ash) compared with the findings by Curran et al (1986). Aubourg (2004a, b) reported that the chemical composition of horse mackerel was 74-76.80% moisture, and 2.2-0.70% total fat.…”
Section: Proximate Compositionmentioning
confidence: 70%